Preparation of pentagamaboronon-0 and its fructose and sorbitol complexes as boron carrier for boron neutron capture therapy (BNCT) application - Ratna Asmah Susidarti; Rohmad Yudi Utomo; Lailatul Qodria; Ratna Dwi Ramadani; Youichiro Ohta; Yoshihide Hattori; Mitsunori Kirihata; Edy Meiyanto (Wolters Kluwer Medknow Publications, 2019)
Development of specific and selective boron carriers is indispensable for boron neutron capture therapy (BNCT) application. Pentagamaboronon-0 (PGB-0) is a promising candidate as boron carrier compound due to the low but selective cytotoxicity in breast cancer cells. Formerly we reported synthesis of PGB-0 which was ineffective due to its low aqueous solubility. In the present study, we, therefore, introduced the new PGB-0 preparation complexed with sugars to increase its solubility in water. By synthesizing at room temperature and using flash chromatography for the purification, we produced PGB-0 with a yield of 40%. PGB-0 fructose complex (PGB-0-F) and PGB-0 sorbitol complex (PGB-0-Sor) were obtained with smaller particle size compared to PGB-0 suspension in water. Based on the MTT assay, the cytotoxicity of PGB-0-F and PGB-0-Sor were higher than PGB-0 even though still categorized as low cytotoxic agents. In conclusion, we provided PGB-0 with a new method and improved its solubility in water. Further investigations are still needed to develop more efficient PGB-0 as boron carrier for BNCT in various cancers.